Fibre architecture modification to improve the tensile properties of flax-reinforced composites. (February 2020) - Rayyaan, Rishad; Kennon, William Richard; Potluri, Prasad; Akonda, Mahmudul
As far as the tensile properties of natural fibres as reinforcements for composites are concerned, flax fibres will stay at the top-end. However, an efficient conversion of fibre properties into their corresponding composite properties has been a challenge, due to the fibre damages through the conventional textile methods utilised to process flax. These techniques impart disadvantageous features onto fibres at both micro- and meso-scale level, which in turn degrade the mechanical performances of flax fibre-reinforced composites (FFRC). Undulation of fibre is one of those detrimental features, which occurs during traditional fibre extraction from plant and fabric manufacturing routes. The undulation or waviness causes micro-compressive defects or 'kink-bands' in elementary flax fibres, which significantly undermines the performances of FFRC. Manufacturing flax fabric with minimal undulation could diminish the micro-compressive defects up to a substantial extent. In this research, nonwoven flax tapes of highly aligned flax fibres, blended with a small proportion of polylactic acid have been manufactured deploying a novel technique. Composites reinforced from those nonwoven tapes have been compared with composites reinforced with woven Hopsack fabrics and warp knitted unidirectional fabrics from flax, comprising undulating fibres. The composites reinforced with the highly aligned tapes have shown 33% higher fibre-bundle strength, and 57% higher fibre-bundle stiffness in comparison with the composites reinforced with Hopsack fabric. The results have been discussed in the light of fibre undulation, elementary fibre individualisation, homogeneity of fibre distribution, extent of resin rich areas and impregnation of the fibre lumens.